Evaluation of antiarthritic activity of ginkgolic acid against Freund's adjuvant induced arthritic rat model - Ziqiang Zhang; Xiaogang Wang; Pengshan Li; Minghua Bai; Wenbing Qi (Universidade de São Paulo, 2021)
This study aimed to analyze the antiarthritic activity of ginkgolic acid against the Complete Freund's Adjuvant (CFA)-induced arthritis in rats. Arthritis was induced through an intradermal injection of CFA (0.1 mL) at the right hind footpad of adult Wistar Albino rats. Ginkgolic acid was administered orally at doses of 25 mg/kg and 50 mg/kg, respectively, once daily via gavage for 25 days upon inducing arthritis. Indomethacin was administered orally at a dose of 3 mg/kg twice in a week which served as positive control group. The animals were sacrificed and subjected to biochemical and histopathological analysis upon completion of treatment. Ginkgolic acid was able to reverse the arthritic effect (p < 0.01) induced by CFA in a dose dependent manner. Swelling of paw, thymus and spleen index, serum biomarker levels, and pro-inflammatory cytokines were significantly reduced (p < 0.01) by the acid whereas the antioxidant enzyme activities were remarkably restored. The histopathological findings were in agreement with the biochemical results. The results indicate that the antioxidant and anti-inflammatory properties of ginkgolic acid can be credited to the antiarthritic effects, and it can be promoted as a potential agent for therapeutic use against osteoarthritis.